SOCIAL CAMPAIGN DESIGN ABOUT THE STORY OF SUNDANESE PANTUN CIUNG WANARA FOR TEENAGERS IN BANDUNG - Purmaningrum Maeni; Hastami Sekar Zahtia; Hadiansyah Hedi (Universitas Pasundan, 2023)
Teenagers are the next generation that will have to bequeath culture to the next generation. Without sufficient understanding, the influence of incoming foreign cultures could replace the local culture. The era of digitalization and culture that also continues to develop should be harmonized. In the sphere of literacy, the era of digitalization brings influence and change to comics. Digital comics that elevate the stories and cultural traditions of a particular region is one example of a form of cultural rejuvenation. Like Metalu Kyoyuzuki's digital comics, 7 Wonders which tells the story of Jaka Tarub, has been liked 9.7 million times with a rating of 9.82 out of 10 since its first airing in July 2016 (cnnindonesia.com: 2020). Folklore itself is a cultural expression of a society through the language of speech that is directly related to various aspects of culture. Broadly speaking, the values in Sundanese culture are reflected through the daily life of the people who live the philosophy of living silih asah, silih asih and silih asuh. In addition, unlike Pantun Melayu, Sundanese pantun story is part of mythical folklore and is considered sacred because it contains a moral message; emotionally; and other life values. The data supporting this research were obtained through literature studies and interviews of resource persons to understand about Ciung Wanara culture and stories. While the determination and data of target audience segmentation is obtained through questionnaires and observations. The rejuvenation of the form and media that packaged the story was conveyed through a social campaign aimed at the late teenagers in Bandung. This campaign is a forum to remind, invite and encourage targets to pay more attention and understand the local culture through exciting new forms of media.